Conventional and exergetic life cycle assessment of organic rankine cycle implementation to municipal waste management: the case study of Mae Hong Son (Thailand) - Surat Sedpho (2018)
© 2016, Springer-Verlag Berlin Heidelberg. Purpose: The critical issue of waste management in Thailand has been rapidly increasing in almost all of the cities due to the economic growth and rising population that could double the amount of solid waste in landfill area. The alternative ways of waste treatment that have more efficiency and effectiveness in terms of energy, ecology, and resources become the key issue for each municipality to replace the old fashioned technology and be able to enhance the ability of solid waste problem management. Waste to energy is one of the favorable approaches to diminish the amount of waste to landfill and utilize waste for electricity. The aim of this study is to identify and quantify the life cycle impacts of the municipal solid waste (MSW) of Mae Hong Son municipality (MHSM), and the case study is the selected waste treatment technology of the Refuse-Derived Fuel (RDF) hybrid with 20 kW of Organic Rankine Cycle (ORC). Methods: The functional unit is defined as 1 t of MSW. The energy, environment, and resource impacts were evaluated by using Life Cycle Assessment (LCA); ReCipe and Net Energy Consumption were referred to calculate the environmental impacts and the benefits of energy recovery of WtE technology. Exergetic LCA was used to analyze the resource consumption, especially land use change. Results and discussion: The results indicated that the environmental impacts were comparatively high at the operation stage of RDF combustion. On the other hand, the production stage of RDF illustrated the highest energy consumption. The ORC power generation mainly consumed resources from material and energy used. The ORC system demonstrated better results in terms of energy and resource consumption when applied to waste management, especially the land required for landfill. Substitution of electricity production from ORC system was the contributor to the reduction of both energy and resource consumption. Installation of spray dry and fabric filter unit to RDF burner can reduce heavy metals and some pollutants leading to the reduction of most of the impacts such as climate change, human toxicity, and fossil depletion which are much lower than the conventional landfill. Conclusions: LCA results revealed that the environmental impacts and energy consumption can be reduced by applying the RDF and ORC systems. The exergetic LCA is one of the appropriate tools used to evaluate the resource consumption of MSW. It is obviously proven that landfill contributed to higher impacts than WtE for waste management.